Juridical Analysis of Online Gambling Crimes from the Perspective of the Criminal Code (KUHP) and the ITE Law: A Study of Decision No. 36/Pid.Sus/2025/PN MJY - Idris Wasahua; Iqbal Hidayatullah (Eduvest - Journal of Universal Studies, 2026)
The development of information technology has expanded the forms and modes of gambling conducted through electronic systems, thereby requiring adjustments in the framework of regulation and the application of criminal law. This research aims to analyze the regulation of gambling offenses from the perspectives of the KUHP and the UU ITE, as well as to examine the application of Article 45 paragraph (3) in conjunction with Article 27 paragraph (2) of the UU ITE to the defendant in the said decision based on the prevailing legal normative construction. The research method used was normative legal research with a statutory approach and a case approach, conducted through the examination of statutory regulations, criminal law doctrines, and legal considerations contained in court decisions. The results of the research show that the KUHP as lex generalis regulates gambling by emphasizing acts of providing, giving opportunities, as well as participating in gambling activities as regulated in Article 303 and Article 303 bis of the KUHP. Meanwhile, the UU ITE as lex specialis contains regulations concerning acts of distributing, transmitting, or making accessible electronic information containing gambling content as regulated in Article 27 paragraph (2), which conceptually are directed at parties who act as providers, operators, or facilitators of online gambling. This research affirms that the differences in regulatory character between the KUHP and the UU ITE require a systematic legal interpretation of the function and purpose of each norm.